1996
DOI: 10.1254/jjp.71.21
|View full text |Cite
|
Sign up to set email alerts
|

Competence Effect of Basic Fibroblast Growth Factor on Cell Cycle in Subcultured Endothelial Cells of Rat Aorta by Flow Cytometry

Abstract: ABSTRACT-With flow cytometry, we investigated the effect of basic fibroblast growth factor (bFGF)-induced competence in subcultured endothelial cells (EC) (4-9-passage) of rat thoracic aorta. The cell population in each phase of the cell cycle was determined by a double staining technique with fluorescein isothiocyanate-conjugated mouse monoclonal antibody against the proliferation-associated nucleus antigen Ki-67 and propidium iodide for total DNA content. EC were cultured in medium containing 5% fetal bo vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…After a 5-day culture with 10% FBS-DMEM and the subsequent 2-day culture under serum-starvation, most of EC population were distri buted at the Go phase of the cell cycle (Fig. 4a) by gating analysis of green fluorescence of FITC bound to Ki-67 and red fluorescence of PI bound to DNA as shown previously (8). The percentages of cell population at each phase relative to the total number of EC were estimated to be 84.9± 1.1 % at the Go phase, 4.6±0.4% at the G1 phase, 7.4± 1.0% at the S phase, 5.2±0.4% at the G2/M phases (n = 3).…”
Section: Western Blot Analysis Determining the Existence Of Pdgf P-resupporting
confidence: 61%
See 2 more Smart Citations
“…After a 5-day culture with 10% FBS-DMEM and the subsequent 2-day culture under serum-starvation, most of EC population were distri buted at the Go phase of the cell cycle (Fig. 4a) by gating analysis of green fluorescence of FITC bound to Ki-67 and red fluorescence of PI bound to DNA as shown previously (8). The percentages of cell population at each phase relative to the total number of EC were estimated to be 84.9± 1.1 % at the Go phase, 4.6±0.4% at the G1 phase, 7.4± 1.0% at the S phase, 5.2±0.4% at the G2/M phases (n = 3).…”
Section: Western Blot Analysis Determining the Existence Of Pdgf P-resupporting
confidence: 61%
“…PDGF induces the com petence in quiescent Balb/c 3T3 fibroblasts as well as bFGF (11). We have previously reported that bFGF stimulates the Go-arrested population of proliferative EC of rat aorta in the 5-day culture to promote enterance into the G1 phase, as a competence factor (8). In contrast, the present study shows that PDGF-BB inhibited the compe tence of the angiogenic EC growth by blocking the tran sition from the Go to G1 phase after a long-time culture (35 days).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation